2014
DOI: 10.1097/lbr.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Tracheal Bronchus in Pediatric Patients Undergoing Rigid Bronchoscopy

Abstract: TB is a relatively common congenital endoscopic lower airway anomaly in childhood, which is itself rarely symptomatic, but almost always coexists with other congenital anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 23 publications
2
32
2
3
Order By: Relevance
“…In our study, a prevalence of type I TB could be observed which is known to create higher frequently anesthetic problems due to cannulation trouble during intubation, impeding correct lung ventilation, unlike observations of patients suffering from tracheal bronchus type 2 or type 3 [2,10]. Despite this higher incidence of type 1 TB in our cohort, no anesthesic problems due to tracheal intubation were described.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In our study, a prevalence of type I TB could be observed which is known to create higher frequently anesthetic problems due to cannulation trouble during intubation, impeding correct lung ventilation, unlike observations of patients suffering from tracheal bronchus type 2 or type 3 [2,10]. Despite this higher incidence of type 1 TB in our cohort, no anesthesic problems due to tracheal intubation were described.…”
Section: Discussioncontrasting
confidence: 81%
“…2). TB was also commonly observed in children with congenital heart disease (19.2%) as described by others [10,17,18].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Right bronchial lengths correlated considerably less with age or height compared to those on the left side. This is not surprising, as the offshoot of the upper right bronchus is very variable and results in about 1% of the normal population in a tracheal bronchus (pig lobe), whereas on the left side, the offshoot of the left upper lobe bronchus is relatively consistent. So far there are no data available that systematically compares bronchial lengths with age, height, or weight.…”
Section: Discussionmentioning
confidence: 90%
“…Recognition of a BB by various imaging modalities such as MDCT can be delayed by misinterpretation of the pseudocarina as the normal tracheal bifurcation, the RMB being identified as the tracheal bronchus (TB) (an aberrant bronchus arising from the trachea) . The TB is a congenital anomaly in which an RUL bronchus has its origin in the trachea rather than at the carina . It can complicate endotracheal intubation, because its cannulation can obstruct the ventilation of the rest of the lung and increase the risk of pneumothorax.…”
Section: Resultsmentioning
confidence: 99%